Laparoscopic repair of inguinal hernias - Sivozhelezov, A. V.; Sykal, N. A.; Chugaj, V. V.; Tonkoglas, A. A. (Journal of Education, Health and Sport, 2017)
The problem of surgical treatment of inguinal hernias over the last 25 years has gone through global changing. Tension free correction of defects of the anterior abdominal wall with using of synthetic prostheses are now the undisputed favorites in the treatment of inguinal hernias. After Lichtenstein operation, Laparoscopic hernia repair now occupies the second place in the structure of operations for inguinal hernias. In 2011, laparoscopic hernioplasty TAPP were performed on 149 patient. The authors did not mention severe intra- or postoperative complications, as well as the conversion to open surgery at failure during laparoscopic surgery. From intraoperative complications they met more often bleeding (4). The greatest technical difficulties arose in damage of inferior epigastric vessels. In the postoperative period they met next complication: the most frequent groin hematoma (4), neuralgia (2) and paresthesias (5), pain in humeroscapular area (4). The laparoscopic techniques of hernia repair are effective, pathogenetically substantiated, provides a comfortable postoperative period and the possibility of early rehabilitation.